Islamic Leadership within the Indonesian Context: Exploring the Relationship between Shura and Pancasila Democracy - Esa Nur Cahyani; Nurul Halifah; Muhammad Hayqel; Ahmadi Ahmadi (The Future of Education Journal, 2026)
This article examines the relevance of shura values in Islamic leadership within the context of Pancasila Democracy in contemporary Indonesia. The study employs a qualitative approach using a normative-empirical method through a literature review of Islamic sources, academic literature, and empirical data related to Indonesia’s political dynamics during the 2019–2024 period. The findings indicate that shura is a fundamental principle of Islamic leadership, grounded in the values of consultation, justice, trustworthiness (amanah), and accountability. Empirical evidence reveals that political leadership in Indonesia continues to face various challenges, including the instrumentalization of religion in politics, integrity crises resulting from corruption practices, and the weakening of public deliberative culture in the digital era. The study further identifies a strong alignment between the principles of shura and the values of Pancasila Democracy, particularly the fourth principle of Pancasila, which emphasizes deliberation and representative decision-making. Based on these findings, the study proposes an integrative leadership model founded on four key pillars: amanah (trustworthiness), shura (consultation), justice, and exemplary leadership. This model is expected to serve as an alternative framework for strengthening the quality of national leadership and promoting a more inclusive, ethical, and public-oriented democracy in support of Indonesia Emas 2045. The study contributes to the discourse on Islamic political thought and democratic governance by demonstrating the compatibility between Islamic leadership values and Indonesia’s democratic principles.